2017
DOI: 10.1007/s40801-017-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Satisfaction During Sublingual Immunotherapy with a Five-Grass Pollen Tablet for Allergic Rhinoconjunctivitis: A Prospective, Non-Interventional Study

Abstract: BackgroundSublingual immunotherapy (SLIT) is a safe/well-tolerated alternative to allergen injection immunotherapy for allergic rhinoconjunctivitis (ARC). Patient adherence is essential and patient-related outcome measures including treatment satisfaction are informative/indicative of adherence.ObjectiveThe aim was to assess treatment satisfaction with five-grass pollen tablet SLIT under real-life conditions.MethodsTreatment satisfaction among adults taking SLIT with a five-grass pollen tablet for grass pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…[8][9][10][11] The high levels of treatment satisfaction observed during 300 IR 5-grass SLIT treatment in Australian SAR patients likewise reinforce the outcomes of large observational studies in Europe, where 300 IR 5-grass SLIT treatment was also shown to be associated with high levels of treatment satisfaction. 17 The observed seasonal patterns of grass pollen counts may assist in understanding why 300 IR 5grass SLIT treatment was similarly effective in all patient subgroups analysed, stratified by polysensitization status to subtropical grass pollen and by geographical location (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[8][9][10][11] The high levels of treatment satisfaction observed during 300 IR 5-grass SLIT treatment in Australian SAR patients likewise reinforce the outcomes of large observational studies in Europe, where 300 IR 5-grass SLIT treatment was also shown to be associated with high levels of treatment satisfaction. 17 The observed seasonal patterns of grass pollen counts may assist in understanding why 300 IR 5grass SLIT treatment was similarly effective in all patient subgroups analysed, stratified by polysensitization status to subtropical grass pollen and by geographical location (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
“…The primary study objective was to investigate in a real-life setting patient satisfaction during the last 3 months of the pollen season (regarding symptom improvement, ease of use, frequency of dosage) following 300 IR 5-grass SLIT treatment using a modified QUARTIS questionnaire (a validated self-report questionnaire that is used to assess patient-reported outcomes in patients with AR who are treated with SLIT) 16 , 17 over a full treatment course of 3 pollen seasons. Patient-reported satisfaction was documented retrospectively at V2, V4, and V6 on 3 measures: (i) symptom improvement ("much more than/more/just as/less than/much less than, I hoped"); (ii) ease of use ("very satisfied/satisfied/neither satisfied or dissatisfied/dissatisfied/very dissatisfied"); and (iii) frequency of dosing ("very satisfied/satisfied/neither satisfied or dissatisfied/dissatisfied/very dissatisfied").…”
Section: Methodsmentioning
confidence: 99%
“…Economic and cost-effectiveness studies from Germany [14] and Canada [15] have shown that the pre-and coseasonal administration schedule of the 5-grass pollen SLIT tablet appears to be associated with lower annual costs versus perennial administration of the 1-grass pollen SLIT tablet, with annual relative savings estimated at €1,142 and Canadian $1,168, respectively [14,15]. Moreover, compliance with the pre-/coseasonal regimen is high [16]. This has even been demonstrated in a study that administered the 1-grass pollen SLIT tablet to allergic patients according to a pre-and coseasonal schedule instead of the recommended perennial schedule [17]; in this study, compliance ranged from 72% in the first year of treatment to 90% by the third year of treatment [17].…”
Section: Tablet Potency and Administration Regimenmentioning
confidence: 99%
“…The results showed that SLIT approximately halved the symptom-medication scores compared to the score registered in drug-treated patients. Since then, several real-life studies were performed, including 11 studies on SCIT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), 15 on SLIT (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and 5 on both (30-…”
Section: Real-life Studies On Aitmentioning
confidence: 99%